ASSESSMENT OF THE INFLUENCE OF THE OPERATING MODES OF THE ELECTRIC TRACTION SYSTEM ON LOSSES FROM UNEVENNESS OF ELECTRICITY CONSUMPTION AND MEASURES TO REDUCE THEM (Transport systems and technologies, 2022)
The article considers the current problem of uneven electricity consumption in railway transport and steps to reduce it. The analysis of conditions of operation of traction rolling stock is carried out. Based on the results of the analysis, the characteristics of the modes of operation of traction rolling stock of railway transport and energy processes in the system of electric traction during their implementation are given. The factors that lead to energy losses due to uneven traction power consumption are presented. Indicators for estimating the unevenness of traction electricity consumption in the case of the subway and suburban rail transport are proposed. The use of integrated energy indicators peak factor and shape coefficient is proposed as indicators. The peak factor characterizes the level of excess power of the power supply system, the shape coefficient - losses in the traction power supply system. According to these indicators, the time diagrams of electricity consumption at the feeder of the railway traction substation and the subway electric train were evaluated. The results of the quantitative assessment confirmed the adverse effect of certain factors on the unevenness of traction power consumption. It was found that the modes of operation of the subway electric train provoke more significant energy losses in the elements of the traction power supply system compared to the railway. It is proved that regenerative braking increases the unevenness of energy consumption, increasing the load on the traction network and contributing to the emergence of pulsed currents in the traction power supply system. Concepts for overcoming the problems of uneven traction power consumption and the use of excess energy recovery are based on the use of energy storage as an additional power source for traction drive.
Keywords: mode of operation, uneven power consumption, losses, peak factor, shape coefficient, energy storage.